2019
DOI: 10.1371/journal.pbio.3000102
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of bacteria in the gut microbiome within and across hosts

Abstract: Gut microbiota are shaped by a combination of ecological and evolutionary forces. While the ecological dynamics have been extensively studied, much less is known about how species of gut bacteria evolve over time. Here, we introduce a model-based framework for quantifying evolutionary dynamics within and across hosts using a panel of metagenomic samples. We use this approach to study evolution in approximately 40 prevalent species in the human gut. Although the patterns of between-host diversity are consistent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
487
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(530 citation statements)
references
References 88 publications
42
487
1
Order By: Relevance
“…The combination of these two effects could allow strains of the same species to coexist, within the gut microbiota, for extended periods with complex temporal dynamics. The few available data on temporal dynamics of genetic polymorphism in species of human gut commensals is starting to confirm this prediction, at least for some species [5][6][7][8]59]. As genetic diversity can impact community composition [82], more time series data, similar to that obtained here, is needed towards a full understanding of the selective mechanisms that shape the eco-evolutionary dynamics within the microbiota [83,84].…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The combination of these two effects could allow strains of the same species to coexist, within the gut microbiota, for extended periods with complex temporal dynamics. The few available data on temporal dynamics of genetic polymorphism in species of human gut commensals is starting to confirm this prediction, at least for some species [5][6][7][8]59]. As genetic diversity can impact community composition [82], more time series data, similar to that obtained here, is needed towards a full understanding of the selective mechanisms that shape the eco-evolutionary dynamics within the microbiota [83,84].…”
Section: Resultssupporting
confidence: 52%
“…Moreover, despite the gap in knowledge of the causes of polymorphism in commensal bacteria [57], its high level indicates that deleterious mutations should typically have small effects [58,59]. Remarkably, by analysing polymorphism patterns in species of the human gut microbiome (including E. coli ), Garud et al [5] recently estimated s d / μ = 10 5 ( μ -mutation rate per site). This implies a s d~ 10 -5 , which is fully consistent with our results (with μ = 10 -10 , as estimated for E. coli from mutation accumulation experiments coupled with whole-genome sequencing; [60]).…”
Section: Survival Of Hypermutators Indicates That Deleterious Mutatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Due to our co-evolution with our gut ecology [31], the gut microbiota's ability to rapidly respond to dietary changes may be reflective of our volatile hunter-gatherer dietary intake that was based on necessity for dietary flexibility with periods of feast and famine [18]. One longitudinal study involving daily gut microbiota investigations of two individuals over the course of a year found that changes in fibre intake are positively correlated with a change in abundance of 15% of the microbial community the following day [5].…”
Section: The Gut Microbiota Responds Rapidly To Dietary Changesmentioning
confidence: 99%
“…A recent study [31] focused on the most abundant strains from gut microbiomes and limited inquiries to hosts with lineages of bacteria whose genetic structure was simple so that it was possible to assign alleles to a dominant lineage with high confidence. With focus on 40 prevalent species from hundreds of previously published human stool metagenomes-with some samples taken at multiple time points-Garud et al [31] drew numerous inferences concerning evolutionary and ecological dynamics. Many findings are worth noting.…”
Section: Dynamics From Genomics and Metagenomicsmentioning
confidence: 99%